(untitled) (Spectrum of Humanities and Social Sciences, 2025)
The study aims to evaluate the status of solid waste management, public awareness towards it, and in reference to the policy frameworks of waste management in a municipality of Karnali province, Nepal. Moreover, it investigates individuals’ knowledge, practices, and local policies related to domestic solid waste management. The study employed descriptive and analytical survey research design. Data were collected through orally administered questionnaire and site observations. The data were collected from 347 households of four communities. The findings revealed that most residents separate their waste into biodegradable and non-biodegradable categories. They composted biodegradable waste at home and collected non-biodegradable waste to send away using the municipality’s vehicle. However, they faced challenges in waste management because of the irregularity of municipality’s waste collection truck. Proper household solid waste management is essential for achieving the sustainable cities and communities. The study recommends that municipality should pay attention to set up the waste management plant particularly for the households’ solid waste for human health and the environment.